Using personal monitoring data to derive organ doses for medical radiation workers in the Million Person Study—considerations regarding NCRP Commentary no. 30. (26th February 2021) - Yoder, C; Balter, S; Boice Jr, J D; Grogan, H; Mumma, M; Rothenberg, L N; Passmore, C; Vetter, R J; Dauer, L T
Abstract: The study of low dose and low-dose rate exposure is of central importance in understanding the possible range of health effects from prolonged exposures to radiation. The One Million Person Study of Radiation Workers and Veterans (MPS) of low-dose health effects was designed to evaluate radiation risks among healthy American workers and veterans. The MPS is evaluating low-dose and dose-rate effects, intakes of radioactive elements, cancer and non-cancer outcomes, as well as differences in risks between women and men. Medical radiation workers make up a large group of individuals occupationally exposed to low doses of radiation from external x-ray/gamma exposures. For the MPS, about 100 000 United States medical radiation workers have been selected for study. The approach to the complex dosimetry circumstances for such workers over three to four decades of occupation were initially and broadly described in National Council on Radiation Protection and Measurements (NCRP) Report No. 178. NCRP Commentary No. 30 provides more detail and describes an optimum approach for using personal monitoring data to estimate lung and other organ doses applicable to the cohort and provides specific precautions/considerations applicable to the dosimetry of medical radiation worker organ doses for use in epidemiologic studies. The use of protective aprons creates dosimetric complexity. It is recommended that dose values from dosimeters worn over a protective apron be reduced by a factor of 20 for estimating mean organ doses to tissues located in the torso and that 15% of the marrow should be assumed to remain unshielded for exposure scenarios when aprons are worn. Conversion coefficients relating personal dose equivalent, H p (10) in mSv, to mean absorbed doses to organs and tissues, D T in mGy, for females and males for six exposure scenarios have been determined and presented for use in the MPS. This Memorandum summarises several key points in NCRP Commentary No. 30.